Perkembangan Intelektual Anak sebagai Dasar Optimalisasi Potensi Belajar di Sekolah Dasar - Qodri, Laura Lailatul; Neviyarni, Neviyarni; Zen, Zelhendri (TSAQOFAH, 2025)
Children’s intellectual development plays a crucial role in supporting the success of learning processes at the elementary school level. This study aims to systematically examine the optimization of intellectual development in children through the implementation of appropriate instructional strategies. A Systematic Literature Review (SLR) was conducted, analyzing five scholarly articles published between 2019 and 2024. The results indicate that instructional strategies such as contextual approaches, problem-based learning, the use of interactive media, and the creation of supportive learning environments have proven effective in fostering students’ logical, critical, and analytical thinking skills. The findings also highlight that teachers' understanding of children’s cognitive development stages is a key factor in designing suitable and effective learning experiences. The study concludes that aligning teaching methods with students’ intellectual development needs is essential for maximizing their learning potential in elementary education. The implication is that teachers must possess adaptive pedagogical competencies to create learning processes that are relevant and oriented toward cognitive development.